Probe Sonicated Synthesis of Bismuth Oxide (Bi2O3): Photocatalytic Application and Electrochemical Sensing of Ascorbic Acid and Lead. (12th February 2022) - Kusuma, K. B.; Manju, M.; Ravikumar, C. R.; Dileepkumar, V. G.; Kumar, A. Naveen; Santosh, Mysore Sridhar; Murthy, H. C. Ananda; Gurushantha, K.
Abstract : A simple and low-cost and highly calibrated probe sonication method was used to prepare bismuth oxide nanoparticles (Bi2 O3 NPs). The formation of a well-crystalline sample at the end of the product has been further calcined at 600°C for 2 hrs. The powder X-ray diffraction (PXRD) patterns of the NPs substantiated the monoclinic structure (space group P21 /c), and the average crystallite size was found to be 60 nm, which was also confirmed by transmission electron microscopic (TEM) studies. Scanning electron microscopic (SEM) images depicted highly porous Bi2 O3 NPs with little agglomeration. Utilizing diffused reflectance spectra (DRS) data, the energy bandgap (E g ) value of 3.3 eV was deduced for Bi2 O3 NPs, and their semiconductor behavior has been confirmed. Two dyes, methylene blue (MB) and acid green (AG) were utilized for degradation studies using Bi2 O3 NPs under UV light irradiation (from 0 to 120 min). The photocatalytic degradation was found to be maximum for MB (93.45%) and AR (97.80%) dyes. Cyclic voltammetric (CV) and sensor studies using the electrochemical impedance spectroscopy (EIS) were performed. The specific capacitance value of 25.5 Fg -1 was deduced from the cyclic voltammograms of the Bi2 O3 electrode in 0.1 N HCl with a scan rate of 10 to 50 mV/s. From the obtained EIS data, the Bi2 O3 electrode showed pseudocapacitive characteristics. The prepared electrodes also exhibited high sensitivity towards the detection of ascorbic acid and lead. Hence, sonochemically synthesized Bi2 O3 NPs are possibly hopeful for excellent photocatalytic and electrochemical sensing of biomolecules.